Enhancing Students’ Information Literacy Through Resource-Based Learning in Respiratory System Learning - Liah Badriah; Aulia Qurrotu Aini; Egi Nuryadin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Information literacy is essential for understanding complex biological concepts, yet instructional approaches that effectively support this competency require further examination. This study investigated the effect of resource-based learning on eleventh-grade students’ information literacy during respiratory system instruction. A quasi-experimental pretest–posttest non-equivalent control group design was employed with 64 students from two science classes. Students’ information literacy was measured using a 30-item multiple-choice test developed according to the Association of College and Research Libraries framework. The instrument was reported as valid and demonstrated acceptable reliability, with a Cronbach’s alpha coefficient of 0.82. Post-intervention data were analyzed using analysis of covariance while controlling for initial scores. Students taught through resource-based learning achieved significantly higher information literacy scores than those taught through discovery learning, F = 5.42, p = 0.021, partial η² = 0.08. These findings indicate that resource-based learning can support students’ information literacy in biology instruction by engaging them in locating, comparing, evaluating, and synthesizing information from multiple resources. Its implementation, however, requires appropriate instructional management to address limited teaching time and technical constraints